2021
DOI: 10.1039/d1cp00842k
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasively improving the Schottky barrier of MoS2/metal contacts by inserting a SiC layer

Abstract: The contact properties of MoS2/metal interfaces are improved by 2D insertions. Moreover, if Al, In, Mg, and Ag are used as the electrodes, the systems are transferred into Ohmic contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The H B and W B values of the Ti 3 C 2 F 2 /SiC, Ti 3 C 2 O 2 /SiC and Ti 3 C 2 (OH) 2 /SiC contacts are summarized in Table 3. T B is defined as 12 where m and ħ are the free electron mass and Planck's constant/2π, respectively. The calculated T B of the Ti 3 C 2 F 2 /SiC, Ti 3 C 2 O 2 /SiC and Ti 3 C 2 (OH) 2 /SiC contacts from eqn (6) are also listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The H B and W B values of the Ti 3 C 2 F 2 /SiC, Ti 3 C 2 O 2 /SiC and Ti 3 C 2 (OH) 2 /SiC contacts are summarized in Table 3. T B is defined as 12 where m and ħ are the free electron mass and Planck's constant/2π, respectively. The calculated T B of the Ti 3 C 2 F 2 /SiC, Ti 3 C 2 O 2 /SiC and Ti 3 C 2 (OH) 2 /SiC contacts from eqn (6) are also listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…11 In addition, some theoretical studies have also reported that covalent bonds might be formed between conventional metals and 2D semiconductors, resulting in the metallization of 2D semiconductors. 11,12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high contact resistance becomes a bottleneck for the application of 2D materials to FETs. To date, numerous efforts have been made to address this problem, such as the following: decreasing the Schottky barrier height of the metal/semiconductor junction with suitable work function metals; achieving Fermi-level pinning through inserting an insulating tunneling layer between the metal and the semiconductor; , designing contact geometry; phasing engineering a 2D semiconductor into a metallic phase; , and molecular and electrolyte doping of the channel. , Consider the most extensively researched material, MoS 2 , as an example. Leong et al reported that the contact resistance of MoS 2 /nickel-etched-graphene can be reduced to 200 Ω·μm .…”
Section: Introductionmentioning
confidence: 99%
“…The need to optimize the metal-MoS2 heterostructure with the aim of reducing the contact resistance steered the research efforts towards the characterization and detailed analysis of MoS2 contacts with several metal materials [8,9]. In this respect, the lack of dangling bonds at the MoS2 surface have raised expectations for a weak Fermi level pinning (FLP) at the metal-MoS2 interface.…”
Section: Introductionmentioning
confidence: 99%